MARKETING SYSTEM, SEASONAL PRICE VARIATION AND MARKET INTEGRATION OF HILSHA (TENUALOSA ILISHA) FISH IN SOME SELECTED AREAS OF BANGLADESH - Imran Omar1*, Md.; Ariful Haque2, Syed; Rajib Sharker3, Md.; Md. Fakhrul Islam4 & Mohammad Azharul Alam4, and (British Journal of Marketing Studies, 2014)
A study was undertaken to examine the marketing system and price behavior of Hilsha fish in selected areas of Chandpur district of Bangladesh during the month of March-April 2012. The objectives of the study were to estimate costs and margins, seasonal price variation and to test market integration of Hilsha fish. Primary and secondary data were used for this study. The higher marketing cost was incurred by aratdars and the lowest by retailer. On the other hand, retailers earned the highest net marketing margins. Analysis of market integration shows that Hilsha fish market in Bangladesh was well integrated. The findings of the study revealed that the marketing of Hilsha was a profitable business and some recommendations were provided for the improvement of Hilsha marketing in the country.